2020
DOI: 10.1177/1087054720915246
|View full text |Cite
|
Sign up to set email alerts
|

Pathways From ADHD Symptoms to Suicidal Ideation During College Years: A Longitudinal Study on the i-Share Cohort

Abstract: Objective: To estimate the association between ADHD symptoms and suicidal ideation in college students, and to test mediation by depressive symptoms or self-esteem. Method: Based on the i-Share cohort (prospective cohort of 2,331 college students in France). Self-reported measures included ADHD symptoms at baseline, self-esteem and depressive symptoms at 3 months, and suicidal ideation at 1-year follow-up. We conducted path analysis to estimate total, direct, and indirect effect. Results: Participants with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
1
13
0
1
Order By: Relevance
“…The influence of depression in the context of ADHD may place individuals at high risk for SI, plans, attempts, and NSSI. This finding is in concordance with findings presented by Van Eck et al (2015) , Arsandaux et al (2021) , and Zhong et al (2021) . Furthermore, the current study demonstrates the indirect role that substance use plays in the association between ADHD and SI, plans, and attempts.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The influence of depression in the context of ADHD may place individuals at high risk for SI, plans, attempts, and NSSI. This finding is in concordance with findings presented by Van Eck et al (2015) , Arsandaux et al (2021) , and Zhong et al (2021) . Furthermore, the current study demonstrates the indirect role that substance use plays in the association between ADHD and SI, plans, and attempts.…”
Section: Discussionsupporting
confidence: 94%
“…Direct links between ADHD and suicidality have been reported and even after adjusting for the presence of co-morbid disorders, individuals with ADHD demonstrated an increased risk of suicide ( Chen et al, 2019 ; Eddy et al., 2020 ; Ljung et al, 2014 ). Nevertheless, alternative findings imply that this association is in fact entirely mediated by the presence of co-morbid disorders, particularly mood and anxiety disorders ( Arsandaux et al, 2021 ; Balazs et al, 2014 ; Zhong et al, 2021 ). Indeed, associations between depression and suicidality have been well established and mood and anxiety disorders are some of the strongest predictors of suicidal behavior in young adults ( Boden et al, 2007 ; Wang et al, 2019 ).…”
mentioning
confidence: 99%
“…Low self-esteem is known to be a part of social anxiety, and to overlap with depression, both of which are associated with STB 44 . Self-esteem, which is an important marker of psychological vulnerability in young adults 45 47 has also been found associated with suicidality 48 . Our study showed that self-esteem is an independent and prominent predictive marker of STB and should therefore be used in a screening tool.…”
Section: Discussionmentioning
confidence: 99%
“…Low self-esteem is known to be a part of social anxiety, and to overlap with depression, both of which are associated with STB. 28 Selfesteem, which is an important marker of psychological vulnerability in young adults [29][30][31] has also been found associated with suicidality. 32 Our study showed that self-esteem is an independent and prominent predictive marker of STB and should therefore be used in a screening tool.…”
Section: Discussionmentioning
confidence: 99%